2012
DOI: 10.1159/000336466
|View full text |Cite
|
Sign up to set email alerts
|

Renal Autotransplantation as Savior in Hybrid Surgery for Aortic Aneurysm Repair

Abstract: Renal autotransplantation is a safe and effective procedure to reconstruct the urinary tract. The current indications for autotransplantation include renal vascular disease, severe ureteral damage, tumours of the kidney and ureter, complex nephrolithiasis and retroperitoneal fibrosis. We report a rare case where we had to perform renal autotransplantation along with hybrid surgery for aortic aneurysm repair. To our knowledge, this is the first case report of its kind for this specific condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Renal autotransplantation is a safe and effective procedure to reconstruct the urinary tract. The current indications for autotransplantation include renal vascular disease, severe ureteral damage, tumors of the kidney and ureter, complex nephrolithiasis and retroperitoneal fibrosis [21]. This approach has become the treatment of first choice in the option of extracorporeal repair of the kidney, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Renal autotransplantation is a safe and effective procedure to reconstruct the urinary tract. The current indications for autotransplantation include renal vascular disease, severe ureteral damage, tumors of the kidney and ureter, complex nephrolithiasis and retroperitoneal fibrosis [21]. This approach has become the treatment of first choice in the option of extracorporeal repair of the kidney, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…More common indications to perform renal autotransplantation include renovascular hypertension, extensive ureteral damage and tumours of the kidney and ureter. But autotransplantation can also be used to treat diverse other urological or even vascular conditions, as Rana et al demonstrated successfully in hybrid surgery for aortic aneurysm repair [10] . The renal nutcracker syndrome, a compression of the left renal vein between the aorta and proximal superior mesenteric artery leading to similar symptoms as the LPHS, can also effectively be treated by renal autotransplantation, although, recently a newer method using retroperitoneal laparoscopic extravascular stent placement has been described [11] .…”
Section: Discussionmentioning
confidence: 99%